(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Holiver N. O. Lingvodidactic basis of perspective specialists’ language training. On the basis of scientific information comparative analysis the notions «lingvodidactics», «computer based lingvodidactics» are grounded. The foundations of language personality foreign language competence are considered.